Decentralization policy in Ukraine : quo vadis - Sakhanienko, Sierhiey (Бескиди, 2017)
The question “quo vadis” of the apostle Peter to Christ envisages an offer to muse upon whether the events are developing in the right direction, whether the changes are happening appropriately, whether the defined goals are fair and the values that lay at their basis are convinced. All these questions arise one way or another in the process of any discussions about the process of decentralization.
Keywords: quo vadis; decentralization; 338.244.47(477)